Legal Reform for Gender Equality: The Role of State Institutions and Society in Protecting Domestic Violence Victims in Indonesia - Riko Andriko; Bahrul Fawaid; Adityo Puro Prakoso (JURNAL AKTA, 2025)
Legal protection for victims of Domestic Violence (DV) in Indonesia is supported by Law Number 23 of 2004 concerning the Elimination of Domestic Violence and its implementing regulations, including Government Regulation Number 4 of 2006. This study aims to analyze the effectiveness of the implementation of the Law Number 23 of 2004 and the Law on Criminal Acts of Sexual Violence, identify legal and social barriers, and evaluate the role of state institutions and society in strengthening the victim protection system. The method used is normative juridical through literature review, legal doctrine, regulatory analysis, the National Commission on Violence Against Women's annual report, publications from the Ministry of Women's Empowerment and Child Protection, and court decisions related to domestic violence. The results indicate that although regulations provide a clear legal framework and provide access to services for victims, their implementation is still hampered by weak inter-agency coordination, limited resources, low levels of understanding among officials, and social stigma. These findings underscore the need for an integrated approach between law, education, and society for more responsive, inclusive, and sustainable protection for victims of domestic violence.